Perbedaan Pengetahuan Ibu Hamil Sebelum Dan Sesudah Diberikan Video Edukasi Tentang Tanda Bahaya Kehamilan : Edukasi Kesehatan; Ibu Hamil; Pengetahuan; Tanda Bahaya Kehamilan - Suliastari, Ni Wayan; Astiti, Ni Komang Erny; Sriasih, Ni Gusti Kompiang (JURNAL KEBIDANAN, 2025)
MMR is one of the indicators used to determine the health status of a country. The government's efforts to reduce MMR include optimizing pregnant women's knowledge and the role of husbands and families in recognizing pregnancy danger signs as early as possible and addressing them by bringing the mother to healthcare facilities for assistance. This study is a pre-experimental research with a one-group pretest-posttest design involving 26 respondents. The sampling technique used was purposive sampling. The study was conducted in April at Kediri III Health Center. The median knowledge of pregnant women before the intervention was 73, and after the intervention, it was 87, with a median difference of 14. The normality test using the Shapiro-Wilk test showed that the data were not normally distributed; therefore, the data were analyzed using the Wilcoxon test, resulting in a p-value of 0.000 < 0.05. This study indicates that there is a difference in pregnant women's knowledge about pregnancy danger signs before and after the intervention. It is recommended that the health center share videos about pregnancy danger signs on its social media, so they can be freely accessed by pregnant women. [Heading isi abstract].